Road narratives and hinterland in Brazilian contemporary literature and cinema - Santini, Juliana [UNESP] (Assoc Int Lusitanistas, 2017)
This work presents an analysis of Viajo porque preciso, volto porque te amo, a motion picture by Marcelo Gomes e Karim Ainouz, and Milagre em Juazeiro, a short story by Ronaldo Correia de Brito. The proposed question is how the characteristics of road narratives are related, in both cases, to a revision of the meanings assumed by hinterland during different periods in Brazilian literature and cinema.
Keywords: hinterland; displacement; road narratives